STRATEGI PENGEMBANGAN USAHA TERNAK IKAN KERAMBA DI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Abdurahman Aan; Hamidi Wahyu; Zuryani Hilmah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the strategy of developing keramba fish farming in Bangkinang District, Kampar Regency through the SWOT method. The method used in this research is descriptive and quantitative methods. Quantitative descriptive analysis is a study that uses numbers. The population in the study were all of the Keramba Fish livestock business industry in Bangkinang District, Kampar Regency in 2019 as many as 41 business units. The sampling technique used census techniques, so the samples in the study were 41 business units. The data in this study were analyzed by means of a SWOT analysis. The results of this study indicate that as a whole, based on the results of the research and analysis of the percentage descriptive data, it can be explained that the condition of the human resources in the cage fish farming in Bangkinang District, Kampar Regency is in bad condition. The condition of the tools for processing the cage fish farming business is inadequate or can be said to be bad. Capital condition is in good condition. Marketing conditions are in poor condition. SWOT analysis, a strategy that can be carried out to empower cage fish farming in Bangkinang District, Kampar Regency is to expand the market so that goods are more popular and improve tools for managing fish cages appropriately.Keywords: Strategy, Development, Cage Fish Livestock, SWOT Analysis